2017
DOI: 10.1002/pits.22038
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐method efficacy and fidelity study of Check and Connect

Abstract: The effectiveness of the Check and Connect dropout prevention program was examined, over the course of 2 ½ years, with 54 middle school students from diverse backgrounds experiencing one or more conditions of risk for dropout. Participants were randomly assigned to receive the Check and Connect intervention or business as usual (i.e., control) in sixth grade. Students in the treatment group had significantly better eighth grade attendance than the control. There were no significant differences between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, school-wide support for students' positive behaviors and parents' active affective involvement in their children's schooling can promote success and prevent students from developing a cynical attitude toward school. More targeted and comprehensive approaches include individualized interventions, such as Check & Connect (Christenson, Stout, & Pohl, 2012), which has been shown to increase school attendance among eighth graders (Powers, Hagans, & Linn, 2017). Aligning with the operationalization of affective engagement in the present study, Check & and Connect is based on long-term relationship building; therefore, a minimum two-year intervention period is needed (see Maynard, Kjellstrand, & Thomspon, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, school-wide support for students' positive behaviors and parents' active affective involvement in their children's schooling can promote success and prevent students from developing a cynical attitude toward school. More targeted and comprehensive approaches include individualized interventions, such as Check & Connect (Christenson, Stout, & Pohl, 2012), which has been shown to increase school attendance among eighth graders (Powers, Hagans, & Linn, 2017). Aligning with the operationalization of affective engagement in the present study, Check & and Connect is based on long-term relationship building; therefore, a minimum two-year intervention period is needed (see Maynard, Kjellstrand, & Thomspon, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Thematic analysis connected to each fidelity rating was utilized for the 73 notes justifying scores found in the AFFIRM Fidelity Checklist. Although not necessarily unique in social work fidelity research ( Powers, et al, 2017 ; Odden, et al, 2019 ; Palmer, et al, 2019 ), the mixed-methods approach allowed for a richer understanding of the causes of low and high fidelity scores for particular sessions and was a holistic method to capture the implementation processes and context, the multimodal (audio and written data) ( Craig et al, 2021 ), and triangulate raters’ assigned scores and their notes on their scoring process.…”
Section: Methodsmentioning
confidence: 99%
“…The mentor also frequently communicates with teachers and families about the student’s engagement and, based on the data collected, determines if intensive interventions are needed. Accumulating studies (e.g., Heppen et al, 2018; Maynard, Kjellstrand, & Thompson, 2014; Powers, Hagans, & Linn, 2017; Sinclair et al, 1998; Sinclair, Christenson, & Thurlow, 2005) show that C&C improves students’ school performance and reduces dropout rates.…”
Section: Check and Connect (Candc)mentioning
confidence: 99%
“…Treatment acceptability is often assessed by asking consumers to indicate their opinions about an intervention via a rating scale or interview. To date, among five C&C studies with a randomized control trial (RCT; that is, Heppen et al, 2018; Maynard et al, 2014; Powers et al, 2017; Sinclair et al, 1998; Sinclair et al, 2005), treatment integrity was only reported in two studies (i.e., Heppen et al, 2018; Powers et al, 2017) and treatment acceptability was vacant in all studies.…”
Section: Candc Integrity and Acceptabilitymentioning
confidence: 99%